1996
DOI: 10.1046/j.1365-2796.1996.474825000.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidaemia in renal transplant patients

Abstract: Hyperlipidaemia is prevalent after renal transplantation, and is associated with impaired graft function, hypertension, and with the use of beta blockers and diuretics, but not with the use of cyclosporine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Notably, the HDL cholesterol levels of transplant recipients have been somewhat higher (approximately 55 mg/dL) than the population mean (3,5,26). This is a consequence of the use of corticosteroids, which increase HDL cholesterol levels (27,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the HDL cholesterol levels of transplant recipients have been somewhat higher (approximately 55 mg/dL) than the population mean (3,5,26). This is a consequence of the use of corticosteroids, which increase HDL cholesterol levels (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Dimeny et al reported a mean serum cholesterol level of 262 mg/dL and an LDL cholesterol level of 175 mg/dL at 6 months after transplantation in 105 renal transplant recipients (29). Aakhus et al reported a mean total cholesterol level of 279 mg/dL in 403 transplant patients (26). Aker et al reported similar findings in 427 renal transplant recipients (3), with a mean cholesterol concentration of 273 mg/dL and a mean LDL cholesterol concentration of 189 mg/dL at 24 months after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…They form the backbone of most immunosuppressive regimen, especially in renal transplant recipients. Cyclosporine can cause mild to moderate elevation in both total and LDL cholesterol and serum triglycerides [109][110][111]. Change in serum triglycerides and concomitant lowering of HDL cholesterol is less consistent than elevation in total and LDL cholesterol.…”
Section: Cyclosporinementioning
confidence: 99%
“…Nevertheless, GCs have been shown to increase the energy intake in children with acute lymphoblastic leukemia (32). Obesity after TX has been considered a risk factor for dyslipidemia (33,34). In a previous study from our center, mild hyperlipidemia was a frequent finding in children under MP-AZA-CsA immunosuppression (47-56% after kidney TX), and the risk for dyslipidemia increased with an increasing age at TX (35).…”
Section: Methylprednisolone Exposurementioning
confidence: 99%